2013
DOI: 10.1371/journal.pone.0066007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rice Black-Streaked Dwarf Virus- and Rice Stripe Virus-Derived siRNAs in Singly and Doubly Infected Insect Vector Laodelphax striatellus

Abstract: Replication of RNA viruses in insect cells triggers an antiviral defense that is mediated by RNA interference (RNAi) which generates viral-derived small interfering RNAs (siRNAs). However, it is not known whether an antiviral RNAi response is also induced in insects by reoviruses, whose double-stranded RNA genome replication is thought to occur within core particles. Deep sequencing of small RNAs showed that when the small brown planthopper (Laodelphax striatellus) was infected by Rice black-streaked dwarf vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
94
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 51 publications
(66 reference statements)
9
94
0
2
Order By: Relevance
“…SRBSDV vsiRNAs were predominantly 22 and 21 nt long (Fig. 1B), consistent with the characteristics reported recently for vsiRNAs in SBPHs infected with Rice black streaked dwarf virus, Rice stripe virus, and Himetobi P virus (15)(16)(17), suggesting that a conserved RNAi pathway may be triggered by viral infection of SBPH or WBPH cells.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…SRBSDV vsiRNAs were predominantly 22 and 21 nt long (Fig. 1B), consistent with the characteristics reported recently for vsiRNAs in SBPHs infected with Rice black streaked dwarf virus, Rice stripe virus, and Himetobi P virus (15)(16)(17), suggesting that a conserved RNAi pathway may be triggered by viral infection of SBPH or WBPH cells.…”
Section: Resultssupporting
confidence: 90%
“…The quantity and integrity of RNA were determined with an Agilent 2100 Bioanalyzer (Agilent Technologies). Small RNA library preparation and Solexas sequencing were performed by the Beijing Genomics Institute at Shenzhen as described previously (15,16). Briefly, following PAGE purification of small RNA molecules (18 to 32 nt) and Solexa adaptor ligation to their 5= and 3= ends, they were amplified with the adaptor primers for 17 cycles and fragments of approximately 90 bp (small RNA and adaptors) were isolated from the agarose gel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mode of replication raises an interesting question: do dsRNA viruses escape from dsRNA-mediated antiviral responses, including RNA silencing? Some studies have detected vsRNAs, which are a hallmark of RNA silencing, from dsRNA viruses in insects using next-generation sequencing (NGS), including reoviruses (20)(21)(22), a totivirus (23), and entomobirnaviruses (24,25). These data suggested that encapsidated dsRNA viruses are also a target of RNA silencing.…”
mentioning
confidence: 99%